1975
DOI: 10.2134/jeq1975.00472425000400020029x
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Sewage Sludge and Selected Element Applications to Soil: Effect on Soil and Fescue

Abstract: Effects of additions of sewage sludge from a highly industrialized area of Atlanta, Georgia, N‐P‐K inorganic fertilizers, selected heavy metals, and trace elements were made on 3 by 9 m plastic‐divided plots sodded to fescue (Festuca arundinacea Schreb.) to evaluate accumulations and movement patterns in the soil. Fescue yields and elemental content were also determined. Soil samples taken 17 weeks after the initial sludge treatment showed only slight increases in Cd, Cr, Cu, Pb, and Zn content. One year later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Following the first growing season, the 0:1, 0.5:1 and 1:1 S:B treatments all produced plant yields greater than the 2: I S:B and the fertilized control. While the biosolids treatments elevated extractable metal levels in the soil, they were not above acceptable ranges and did not suppress plant growth or pose bioaccumulation threats (Boswell, 1975). The biosolids amendments improved sciil properties though enhanced organic matter levels and associated physical effects by keeping P available throughout the experiment and by keeping the soil pH higher than the fertilized control.…”
Section: Discussionmentioning
confidence: 89%
“…Following the first growing season, the 0:1, 0.5:1 and 1:1 S:B treatments all produced plant yields greater than the 2: I S:B and the fertilized control. While the biosolids treatments elevated extractable metal levels in the soil, they were not above acceptable ranges and did not suppress plant growth or pose bioaccumulation threats (Boswell, 1975). The biosolids amendments improved sciil properties though enhanced organic matter levels and associated physical effects by keeping P available throughout the experiment and by keeping the soil pH higher than the fertilized control.…”
Section: Discussionmentioning
confidence: 89%
“…Anderson & Nilson (1972) showed that practically all the Mn, Zn, Cu, Ni, Co, Cr, Pb, Cd, Hg, As and Se remained in the upper 0-20 cm of the soil 12 years after adding 84 t ha -1 of sludge. Boswel (1975) found that very little Zn moved deeper than 15 cm in a clay loam soil. The accumulation of Zn, Cu, Ni and Pb in the top layer of the soil can be attributed to the high affinity of the metals to organic matter (McGrath & Lane, 1989).…”
Section: Total Heavy Metals Content and Movement In Soilmentioning
confidence: 95%
“…A discussion of these is outside the scope of this chapter and for detailed information the reader is referred to Chapter 2 and to the following selected publications: Domestic refuse (Purves, 1977) ; domestic coals, coal-burning power stations and fly-ash (Swaine, 1977) ; sewage sludge (Le Riche, 1968;Berrow and Webber, 1972;Berggren and Oden, 1972;Blakeslee, 1973;Nilsson, 1972, 1976;Page, 1974;BoswelL 1975;Dowdy and Larson, 1975;Furr el at., 1976;Berrow and Burridge, 1980); pig slurry (Unwin, 1980); composted town refuse (Purves and Mackenzie, 1973;Gray and Biddlestone, 1980); cadmium in rock phosphate and superphosphate (Williams and David, 1973;Stenstrom and Walter, 1974;Fulkerson. 1975: Commission of the European Communities, 1978): other fertilizers and liming materials (Swaine , 1962).…”
Section: Other Sources Of Metal Pollutionmentioning
confidence: 99%